2009
DOI: 10.1016/s0873-2159(15)30127-6
|View full text |Cite
|
Sign up to set email alerts
|

Influência da função pulmonar e da força muscular na capacidade funcional de portadores de doença pulmonar obstrutiva crónica

Abstract: Our results showed the importance of lower limb muscle strength in submaximal exercise testing. We conclude that femoral quadriceps muscle strength is the only one of the variables studied which can predict the distance COPD patients walk in the 6MWT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
6
0
3
Order By: Relevance
“…Previous studies have shown a correlation between limb muscle strength and functional capacity in both ULs and LLs in people with COPD. 6 , 9 12 Three studies found moderate to strong correlations between maximal quadriceps strength and LL functional capacity 6 , 9 , 10 measured using the 6-minute walk test (6MWT), the timed up-and-go test (TUG), the timed stair climb power test, and the 30-second sit-to-stand test (STS). Janaudis-Ferreira and colleagues 11 found a moderate to strong correlation between limb muscle strength and UL functional capacity measured using the unsupported UL exercise test (UULEX) and the 6-minute pegboard and ring test (6PBRT).…”
mentioning
confidence: 99%
“…Previous studies have shown a correlation between limb muscle strength and functional capacity in both ULs and LLs in people with COPD. 6 , 9 12 Three studies found moderate to strong correlations between maximal quadriceps strength and LL functional capacity 6 , 9 , 10 measured using the 6-minute walk test (6MWT), the timed up-and-go test (TUG), the timed stair climb power test, and the 30-second sit-to-stand test (STS). Janaudis-Ferreira and colleagues 11 found a moderate to strong correlation between limb muscle strength and UL functional capacity measured using the unsupported UL exercise test (UULEX) and the 6-minute pegboard and ring test (6PBRT).…”
mentioning
confidence: 99%
“…A avaliação do nível de gravidade da DPOC nesses pacientes foi analisada, tendo como base a medida do VEF 1 pós o uso do broncodilatador, sendo estabelecida a graduação da obstrução de acordo com a preconizada pela GOLD 14 , uma vez que, "a espirometria é um teste funcional amplamente utilizado, e seus parâmetros, sobretudo o VEF 1 , apresentam boa reprodutibilidade" [2][3][4][5][6][7][8][9][10][11][12][13][14] .…”
Section: Discussionunclassified
“…Sendo assim, este trabalho vai ao encontro do estudo sobre a correlação entre as provas funcionais respiratórias e o teste de caminhada, em que é afirmado que o estímulo verbal adotado pelos examinadores pode ser o responsável pela melhor performance física apresentada pelos pacientes16, ou seja, "durante o TC6m, a estimulação verbal determina melhor rendimento físico em pacientes portadores de enfermidades cardiopulmonares" [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…However, O'Donnell et al 39 demonstrated that FEV 1 is limited when the intent is to predict the capacity for physical efforts because it does not evaluate this condition in a systemic manner, and this finding has since been confirmed by the results of other studies. Moreover, because a decline in the DW in the 6MWT is observed among more serious patients, the DW has been shown to be a more sensitive variable for the detection of clinical changes associated with COPD as compared to the pulmonary function test, thus highlighting its importance for monitoring these patients 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%